Spiritual Pedagogy of the Sufism Model in Pesantren: Effectively Shaping Inclusive and Moderate Character Among Students - Mokhamad Mahrus; Achmad Yusuf; Saifulah; M. Anang Sholikhudin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study analyzes the concept, implementation, and spiritual impact of Sufism pedagogy in shaping inclusive and moderate character among students at the Bahruddin Islamic Boarding School. Employing a qualitative approach with a case study design, data were collected through observation, interviews, and document analysis to address three research questions concerning the conceptual framework, implementation model, and educational outcomes. The findings reveal, first, that the concept is realized through the integration of Sufi moral principles with spiritual practices such as dhikr and muhasabah, transmitted through direct guidance (talaqqi) and the exemplary role modeling (uswah) of the kyai. Second, the model is implemented through a hidden curriculum that instills values of mahabbah (love), tasamuh (tolerance), and tawazun (balance) in daily life, reinforced through dialogue and cross-group social activities. Third, this implementation significantly contributes to the development of more inclusive religious attitudes among students, characterized by appreciation of diversity and commitment to the middle path (wasatiyyah), as reflected in their rejection of extremism. The study concludes that Sufism education based on spiritual pedagogy constitutes an effective holistic model for instilling inclusive and moderate character, offering a relevant framework for strengthening religious moderation in Islamic educational environments.